Depletion of PRDM9 enhances proliferation, migration and chemotaxis potentials in human periodontal ligament stem cells. (2nd September 2020) - Zhang, Jianpeng; Zhang, Chen; Yang, Haoqing; Han, Xiao; Fan, Zhipeng; Hou, Benxiang
ABSTRACT: Purpose: Periodontal ligament mesenchymal stem cells (PDLSCs) are important for periodontal tissue regeneration, but how these cells are regulated remains unclear. PRDM (PRDI-BF1 and RIZ homology domain containing) genes play key roles in cell proliferation and differentiation. The present study aimed to investigate the role of one PRDM gene, PRDM9, in the proliferation, migration and chemotaxis potential of PDLSCs. Materials and methods: Cell proliferation was examined on the basis of the cell doubling time, cell counting kit-8 (CCK8) assays, and flow cytometry analysis of the cell cycle. Gene expression was detected by Western blotting and real-time RT-PCR. Scratch migration and Transwell chemotaxis assays were used to analyse cell migration and chemotaxis abilities. Microarray analysis and ChIP assays were used to examine the downstream genes of PRDM9 and the corresponding mechanism. Results: The results showed that knock-down of PRDM9 enhanced cell proliferation by promoting cell cycle progression and rapid transition from the G1 to S phase via downregulation of p21 and p27 and upregulation of cyclin E. Additionally, depletion of PRDM9 increased the migration and chemotaxis potential of PDLSCs. Microarray results showed that 13 genes, including IGFBP5, IFI44L, and POSTN, were upregulated and 34 genes, including PIP, were downregulated after the depletion of PRDM9. Furthermore, we observed that the depletion of PRDM9 promoted the transcription of IGFBP5 by increasing H3K4me3 methylation in the IGFBP5 promoter. Conclusion: These discoveries indicated that depletion of PRDM9 increased the cell proliferation, migration and chemotaxis potential of PDLSCs and revealed important downstream genes.